The evolution of the resistance of Staphylococcus aureus found on healthcare workers correlated with local consumption of antibiotics - Busato,César Roberto (2006)
OBJECTIVE: Correlate the evolution of the resistance of Staphylococcus aureus collected from healthcare workers with the local consumption of antibiotics. MATERIAN AND METHODS: Open prospective research.Study Site. General Reference Hospital with 200 beds in a 700,000 inhabitant region, in Ponta Grossa, Paraná, Brazil. RESULTS: Two collections (samples) of Staphylococcus aureus isolates were obtained from healthcare-workers during an approximate four-year interval. Samples 1 (n= 200) and 2 (n= 270) had this bacterium in 63 (32%) and 90 (33%) of the patients, respectively. At the same time, the annual consumption of antibiotics in DDD/1,000 patient-days was determined. The variation of resistance was significantly smaller (m.s.d.=12.11) for gentamycin (p<0.01) and (m.s.d.=9.22) for Tobramycin (p<0.05). The correlation between variation in resistance and antibiotic consumption was not significant. Workers studied in the two samples showed a significant (p<0.01) frequency (c²=10.44) for persistent nasal carriage and for non carriage. Methicillin resistant Staphylococcus aureus was found in 12 (6%) patients of sample 1 and 11 patients (4%) of sample 2. CONCLUSION: Stability of resistance allows us to maintain therapeutic outlines. The variation in bacterial resistance in the twice-sampled population (n=105) indicated the selection pressure of the hospital environment. The resistance that was found is representative of the hospital microbiota; this relationship represents a biological model, based on the healthcare-workers' interaction with colonizing bacteria and nosocomial infections. New studies could improve this model for other bacteria, to determine the tendency for resistance and help guide the antibiotic use.